Mechanisms of aerobic exercise effects on the gut microbiota and its metabolites in anxiety disorders - Zheng, Yalin; Qu, Yaqi; Yao, Mingchen; Li, Kaixuan; Dong, Yani; Xing, Xinru; Yang, Tingwu; Guo, Hao; Huang, Peng (Frontiers in Microbiology, 2025)
Anxiety disorders are prevalent and disabling conditions that frequently co-occur with major depression, alcohol and substance abuse disorders, and personality disorders. While psychopharmacological treatments and cognitive-behavioral therapy are the primary interventions for anxiety disorders, up to 30% of patients exhibit inadequate treatment responses, and approximately 40% relapse within the first year after discontinuing medication. Moreover, medication-related side effects have a significant impact on patients’ quality of life. These limitations highlight the urgent need for more comprehensive research into the underlying pathophysiology of anxiety disorders to facilitate the development of more effective therapeutic strategies. In this context, aerobic exercise has consistently been linked to improvements in physical health, life satisfaction, cognitive functioning, and psychological wellbeing. Aerobic exercise may serve as an effective and cost-efficient alternative for managing various anxiety disorders. This review explores the potential mechanisms through which aerobic exercise influences anxiety disorders, focusing on its effects on gut microbiota and related metabolites. The findings aim to propose novel therapeutic strategies for patients with anxiety disorders and provide a theoretical foundation for future research in this field.